ANALISIS FATWA MUI NO. 1/MUNAS VII/MUI/5/2005 TENTANG PERLINDUNGAN HAK KEKAYAAN INTELEKTUAL (HAK CIPTA) DALAM PERSPEKTIF MAṢLAḤAH MURSALAH - Widyastuti, Yuyun (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2020)
Abstract The Council of Indonesian Ulama (MUI) stipulates legal provisions that any violation of Intellectual Property Rights if without legal permission is forbidden in fatwa MUI No.1/MUNAS VII/ MUI/5/2005 concerning protection of Intellectual Property Rights. For this reason, researchers intend to examine it with the aim of: to find out the provisions of the Â Fatwa MUI No.1/MUNAS VII/MUI/5/2005 concerning Intellectual Property Rights protections and to find out Fatwa MUI No.1/MUNAS VII/MUI/5/2005 concerning protection of Intellectual Property Rights (copyright) in the perspective of the maṣlaḥah mursalah. In the legal provisions of the Fatwa MUI No. 1/MUNAS VII/MUI/5/2005 concerning protection of Intellectual Property Rights is still general and more protective of rights holders only, but otherwise does not or does not consider the public interest. This type of research uses library sources, using normativ legal research methods. Then in analyzing the data the authors use content analysis techniques or content studies. From the discussion of this thesis it can be concluded that, the legal provisions in the fatwa MUI No. 1/MUNAS VII/MUI/5/2005 concerning IntellectualÂ Property Rights viewed from the perspective of the maṣlaḥah mursalah, the legal provisions are more protective of the right owner. When viewed in terms of rights users, the benefits are still vague, because there are legal provisions that have illegal status against any violations of Intellectual Property Rights if without permission, even thought the rights user does not aim tobe commercialized. Keywords: Fatwa MUI about HKI, HKI Law provisions, Maṣlaḥah Mursalah. Abstrak Majelis Ulama Indonesia (MUI) menetapkan ketentuan hukum bahwa setiap bentuk pelanggaran Hak Kekayaan Intelektual jika tanpa izin hukumnya haram dalam fatwa MUI No. 1/MUNAS VII/MUI/5/2005 tentang perlindungan Hak Kekayaan Intelektual (HKI). Untuk itu peneliti berkeinginan menelitinya dengan tujuan: Untuk mengetahui ketentuan Fatwa MUI NO. 1/MUNAS VII/MUI/5/2005 tentang Perlindungan HKI, dan untuk mengetahui Fatwa MUI NO. 1/MUNAS VII/MUI/5/2005 tentang Perlindungan HKI (Hak Cipta) dalam perspektif maṣlaḥah mursalah. Dalam ketentuan hukum Fatwa MUI Nomor: 1/MUNAS VII/MUI/5/2005 tentang Perlindungan Hak Kekayaan Intelektual masih bersifat umum dan lebih protektif terhadap pemegang hak saja, akan tetapi sebaliknya tidak atau kurang mempertimbangkan kepentingan umum. Jenis penelitian ini menggunakan penelitian library research, yaitu penelitian yang dilakukan dengan cara menelaah atau mengkaji sumber-sumber kepustakaan, dengan menggunakan metode penelitian hukum normatif. Kemudian dalam analisis data penulis menggunakan teknik content analysis atau kajian isi. Dari pembahasan skripsi ini dapat disimpulkan bahwa, ketentuan hukum dalam fatwa MUI No. 1/MUNAS VII/MUI/5/2005 tentang HKI dilihat dalam perspektif maṣlaḥah mursalah, ketentuan hukumnya lebih protektif terhadap pemilik hak. Jika dilihat dari segi pengguna hak, kemaslahatannya masih samar-samar, dikarenakan terdapat ketentuan hukum yang mempunyai status hukum yang haram terhadap setiap pelanggaran terhadap HKI jika tanpa izin, walaupun si pengguna hak tidak bertujuan untuk dikomersilkan. Kata Kunci: Fatwa MUI tentang HKI, Ketentuan Hukum HKI, Maṣlaḥah Mursalah.